PERAN PEMERINTAH REPUBLIK INDONESIA DALAM PERLINDUNGAN TENAGA KERJA INDONESIA (TKI) SEKTOR INFORMAL DI ARAB SAUDI - Ratu Rayanti Arumsari (Global Political Studies Journal, 2019)
This study aims to determine how the developing country, Indonesia, affected Saudi Arabia to protect the domestic workers. Researcher are trying to understand and analyze how this cooperation in the agreement that related in placement and protection based on the moratory to overcome the violence to indonesian domestic workers. This study used qualitative research type. The research method used is descriptive analysis techniques. Most of the data collected through the literature and websites searching.Those data were analyzed by theory approach based on International Relations, International Cooperation, International Agreement, International Labour Regulation, National Interest and Negotiation Diplomacy. The results of this study show the cooperation between Republic of Indonesia and The Kingdom of Saudi Arabia in the placement and protection of indonesia labours post informal sector workers moratorium, during the process until invent to Memorandum of Understanding.